Euroland: Upswing postponed - Kai Carstensen; Klaus-Jürgen Gern; Christophe Kamps; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2002)
The recovery in Euroland has started at the beginning of this year but it has remained rather moderate. Real GDP increased at an annual rate of less than 1 percent during the first half of 2002. Capacity utilization has declined further and unemployment continued to go up. While exports have gained some strength, domestic demand has just about stabilized. Against the background of weak economic activity the increase in consumer prices has calmed down considerably. Several factors can be made responsible for the sluggish economic performance. Consumer sentiment was affected by the price increases at the beginning of this year and obviously also by the introduction of the new currency. Profit expectations of firms have not improved sufficiently as it is also reflected in the collapse of stock prices. In addition, export expectations have deteriorated recently because of the uncertainty about the US economy and the appreciation of the euro. In the light of the recent turbulences on stock markets and the increased uncertainty about the economic outlook in the euro area, the ECB will probably not raise interest rates this year as was expected a few months ago. In fact, there is a discussion whether the ECB would — or even should — lower interest rates. According to both pillars of its monetary policy strategy, an easing of monetary policy cannot be justified. Money growth still exceeds the reference value by a wide margin. Although our analysis indicates that money demand has become unstable recently, there is a risk that there is some excess liquidity in the euro area and that the high money growth cannot be explained by special factors alone. The perspectives for price level stability have also not improved considerably. The budget deficit in Portugal and also in Germany will probably exceed 3 percent of GDP this year; in Italy and France it is approaching this level. The European Commission has started the excessive deficit procedure for Portugal and may do the same for Germany soon. However, it is not certain there will be the necessary majority in the ECOFIN Council for the decision whether an excessive deficit exists. One cannot exclude that Italy and France have an interest to block such a decision because they also have problems of meeting the obligations of the Stability and Growth Pact. So it is possible that the finance ministers of these four countries which together have 35 votes in the Council will prevent the decision about the excessive deficit procedure. The coming months will show whether the Pact really has teeth. We are strongly in favor of a strict application of the Stability and Growth Pact. The recent deterioration of consumer and business sentiment does not, in our view, imply that a renewed downturn is imminent. After a relatively sluggish growth in the rest of this year, economic activity will pick up considerably in the course of 2003 and real GDP will rise faster than potential output. For the year as a whole, real GDP will increase by 2.3 percent, after 0.8 percent in 2002. The labor market situation will improve slowly in the course of next year. Inflation will remain moderate also because the ECB will tighten monetary policy gradually; in addition we expect that wages will rise only moderately. The consumer price index will increase by 1.6 in 2003, after 2.1 this year.
Keywords: 330; Konjunktur; Konjunkturprognose; Europäische Wirtschafts- und Währungsunion; EU-Staaten